2001
DOI: 10.1046/j.1365-2842.2001.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis on preferable I‐bar clasp shape

Abstract: An I-bar clasp is one of the most popular direct retainers for distal-extension removable partial dentures. However, no adequate information is available on preferable shape as determined by biomechanics. This study aimed (1) to investigate, by finite element analysis (FEA), the dimensions and stress of I-bar clasps having the same stiffness, and (2) to estimate a mechanically preferable clasp design. Three-dimensional FEA models of I-bar clasps were created with vertical and horizontal straight sections conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
3
14
0
Order By: Relevance
“…Polyetheretherketone (PEEK) is a synthetic, tooth colored polymeric material that has been used as a biomaterial in orthopedics for many years with observed mechanical properties, and adequate mechanical stability to justify the basic requirements in the restorative field as showed by recent studies (14,15) . A few studies have reported on the adequate retentive forces required for clasps retention (16,17) . One study stated that 3 to 7.5 N is the retentive force required for adequate retention and functioning of PRDPs, while another study found that 5 N could give an acceptable degree of retention (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Polyetheretherketone (PEEK) is a synthetic, tooth colored polymeric material that has been used as a biomaterial in orthopedics for many years with observed mechanical properties, and adequate mechanical stability to justify the basic requirements in the restorative field as showed by recent studies (14,15) . A few studies have reported on the adequate retentive forces required for clasps retention (16,17) . One study stated that 3 to 7.5 N is the retentive force required for adequate retention and functioning of PRDPs, while another study found that 5 N could give an acceptable degree of retention (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown FEA to be a suitable method for the evaluation of complex geometric models (Sato et al 1995(Sato et al , 1999(Sato et al , 2000(Sato et al , 2001a(Sato et al , 2001b. Previous studies have simulated the application of 5 N loads to RDP clasps (Yuasa et al 1990;Sato et al 1995Sato et al , 2000Sato et al , 2001aSato et al , 2001b.…”
Section: Discussionmentioning
confidence: 99%
“…Bar clasps with a wide range of dimensions are used in clinical applications, and Sato et al (2000Sato et al ( , 2001aSato et al ( , 2001b stated that the ideal bar clasp shape is still unknown. Their studies have shown bar clasp thickness and tapering to be the critical parameters that have a great effect on stress and flexibility, finding specifically that a uniformly tapered bar clasp arm decreases stress concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young's Modulus (MPa) Poisson Coefficient Cortical bone [15][16][17] 13,700 0.3 Cancellous bone [17,18] 1370 0.3 Gingiva [19] 19.6 0.3 [21] 69 0.45 Ceramic [22] 140,000 0.28 Ti-6Al-4V [23] 110,000 0.35 Cement [24] 10,760 0.35 Figure 3. Complete mandible assembly in the simulation environment with applied forces corresponding to pterygoid muscles (P) and the masseter muscles (M) and restrictions at the temporomandibular joint surfaces.…”
Section: Methodsmentioning
confidence: 99%